2018
DOI: 10.1111/modl.12446
|View full text |Cite
|
Sign up to set email alerts
|

Teacher–Student Relationships and L2 Motivation

Abstract: Positive relationships with teachers are important for students' second language motivation. However, little is known about how interpersonal interactions stimulate motivated behavior. Drawing on studies of teacher-student relationships, theories from positive psychology, and the psychology of unconscious selfregulation, this case study examines moments of teacher-student interaction and explores influences on students' engagement and motivation. Observations (N = 15) were carried out in 2 classrooms, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 65 publications
4
81
0
5
Order By: Relevance
“…In educational context, the teacher-student interactions have been acknowledged as a crucial factor for the students to meet the demands of cognitive and affective learning outcomes in school (Cadima et al, 2010;Pennings et al, 2018). Recent research has also recognized that such interpersonal connectedness can positively affect the students" L2 motivation (Henry & Thorsen, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In educational context, the teacher-student interactions have been acknowledged as a crucial factor for the students to meet the demands of cognitive and affective learning outcomes in school (Cadima et al, 2010;Pennings et al, 2018). Recent research has also recognized that such interpersonal connectedness can positively affect the students" L2 motivation (Henry & Thorsen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…as an auspicious tool in increasing the students" motivation. In the context of L2 learning, the greater academic motivation the students have, the greater engagement during lessons they will demonstrate that is closely associated with their academic achievement (Henry & Thorsen, 2018;Lauermann & Barbosa, 2018;Rajab et al, 2012). For this reason, it is considered essential to be integrated into the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of relational histories, each identity orientation taking place when a self-disclosure is made by a teacher can be understood as a micro-accrual in an ongoing process of relationship development. Although these ideas are only beginning to be explored in language learning psychology (Henry and Thorsen 2018), the notion that relationships arise in and from moment-to-moment interactions is well-established in mainstream education research. In work examining teacher-student relationships and influences on students' classroom behaviors, moments during lessons when students experience a close personal connection with a teacher have been shown to have both situational and long-term effects, moments of contact functioning as building blocks from which motivationally-positive relationships are constructed (Korthagen, Attema-Noordewier, and Zwart 2014).…”
Section: Discussion: Conceptualizing Motivational Influencesmentioning
confidence: 99%
“…The data comes from the Motivational Teaching in Swedish Secondary English project where ethnographic observations of secondary school English language lessons in Sweden were conducted. The project methodology is described in Henry and Thorsen (2018) and in the supplementary material.…”
Section: Methodsologymentioning
confidence: 99%
“…In the Motivational Teaching in Swedish Secondary English (MoTiSSE) project, ethnographic research was carried out in the classrooms of 16 English teachers identified as knowledgeable about and interested in students’ out‐of‐school activities involving English, as having a professional practice informed by these insights, and as having students who were generally motivated. A detailed account of the recruitment procedures is provided in Henry and Thorsen (, ).…”
Section: Methodsologymentioning
confidence: 99%